One-stage versus two-stage thoracoscopic surgery for synchronous bilateral pulmonary nodules: a propensity score-matched analysis - Yu Han; Fei Xiao; Qianli Ma; Zhenrong Zhang; Zaiyong Wang; Chaoyang Liang; Deruo Liu (World Journal of Surgical Oncology)
Abstract Background The aim of this study was to compare the surgical efficacy of one-stage and two-stage video-assisted thoracoscopic surgery (VATS) for bilateral multiple pulmonary nodules (BMPNs). Methods A retrospective analysis was made of 156 patients, 84 who underwent one-stage and 72 who underwent two-stage VATS for BMPNs at our department between January 2019 and December 2022. Perioperative and long-term outcomes were compared between the two groups using propensity score-matched (PSM) analysis. Results There were 48 patients in each group after PSM. No significant difference was observed in operation time, blood loss, rates of overall complications, and 3-year overall survival (p>0.05) between one-stage and two-stage groups. The one-stage procedure was associated with shorter length of stay (5 days [IQR 4-5.75 days] vs. 9 days [IQR 7–10 days]; p<0.001), as well as lower total cost (14626.3 ± 4149.4 vs. 18975.9 ± 3720.8 USD, p<0.001) compared to the two-stage procedure. The one-stage group was associated with better 3-year RFS compared with the two-stage group (90.7% vs. 75.3%, p = 0.039). Conclusion One-stage and two-stage VATS for BMPNs are both safe and feasible in selected patients. One-stage procedure possess potential advantages in reducing hospital stay and cost, as well as preventing tumor progression.